INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) USE AMONG HUNGRY RICE (ACCHA) FARMERS IN PLATEAU STATE, NIGERIA - Michael, I. W.; Garba, A.; Hamidu, B. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study examined the information and communication technology used by hungry rice farmers in Jos South and Barikin Ladi Local Government Areas of Plateau State. A multistage sampling procedure was used in selecting 160 respondents as the sample size of the study. A well-structured questionnaire was used for data collection and analysed using both descriptive and inferential statistics. The results showed that 51.9% of the respondents were male while 48.1% were female. Majority (43.75%) were within the age of 20-29 years with a mean age of 35.4 years. The respondents had a mean household size of 7 persons, cultivating an average farm size of 2.43 hectares and had a mean farming experience of 4.40 years in hungry rice farming. The findings revealed that the use of radio, television and mobile phone has increased the income and livelihood of the hungry rice farmers due to new methods learnt from agricultural programmes, also hungry rice farmers have been exposed to latest technology on hungry rice production through watching of documentaries and communicating with other hungry rice farmers and customers. Age, farm size and farming experience were statistically significant (P< 0.01) and (P< 0.05) respectively. The study also revealed that the problems faced by the respondents were irregular power supply (41.3%), high cost of ICT devices (50.0%), and inadequate knowledge on technical know-how (46.3%). The study concluded that age, farm size and farming experience were the factors that influence the use of ICT among Acha farmers in the study area. It was therefore recommended that hungry rice farmers should be encouraged to access and utilize ICTs by supporting them financially and materially by the governments and private sectors/donor agencies and government should improve on electricity supply to the rural areas which will enable the farmers to utilize the ICT devices.